Recent Progress in Molecular Dynamics Simulations of Dihydrofolate Reductase - E. Kerrigan, John; Ercikan Abali, Emine; R. Bertino, Joseph (Current Enzyme Inhibition, 2012)
This brief review will cover recent advances and applications of molecular dynamics simulations of dihydrofolate reductase over the course of the past few years. The application of the technique to the study of kinetic isotope effects, binding free energy of drugs, impact of ligand binding on protein conformation and study of coupled motions in hydrogen tunneling reactions will be discussed.
Keywords: linear interaction energy